2013
DOI: 10.1542/peds.2012-3672
|View full text |Cite
|
Sign up to set email alerts
|

Race and Acute Abdominal Pain in a Pediatric Emergency Department

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Abdominal pain is a frequent complaint in pediatric emergency departments, with a broad differential diagnosis. The impact of demographic and clinical characteristics of patients on the evaluation and management of these children is not well known. WHAT THIS STUDY ADDS:The most common cause of abdominal pain is constipation, which rarely requires hospital admission. Demographic factors, in particular race, do not seem to affect evaluation and management. abstract OBJECTIVE: To inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 18 publications
3
53
2
2
Order By: Relevance
“…10 In the study by Caperell et al, female gender was predominant with 61% in African children and 52% in white children in contrast with male preponderance seen in Asian children as seen in our study and the other study. 1 In the Muhammad et al study the mean age of the children was found to be 9.7 years while in our study the maximum number of patients 41% were in the age group of 10 to 12 years.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…10 In the study by Caperell et al, female gender was predominant with 61% in African children and 52% in white children in contrast with male preponderance seen in Asian children as seen in our study and the other study. 1 In the Muhammad et al study the mean age of the children was found to be 9.7 years while in our study the maximum number of patients 41% were in the age group of 10 to 12 years.…”
Section: Discussioncontrasting
confidence: 39%
“…On an average about 5 to 10% of emergency department visit by children is attributable to abdominal pain. 1 The presentation of abdominal pain can be acute or chronic. Among the acute causes some require urgent treatment while in others the treatment is nonurgent.…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal pain was reported up to 6.2% of all pediatric emergency admissions (2). The most common etiology of acute abdominal pain in pediatric patients is acute appendicitis (3).…”
Section: Introductionmentioning
confidence: 99%
“…6 Akut apandisit acil abdominal cerrahi gerektiren durumların başında gelmektedir ve çocuk acil servise akut karın ağrısı ile başvuruların %1-12'sini oluşturmak-tadır. [7][8][9][10] Çocuklardaki akut karın ağrısına yaklaşımdaki en büyük sorun hastanın cerrahi gerektiren bir durumunun olup olmadığının anlaşılmasındaki güçlüktür.…”
Section: Sonuçlarunclassified
“…Dört yaşından küçük hastalarda perfore apandisit oranı %70-100 arasında bildirilmektedir. 9,11 Bu çalışma ile ilk başvuru sırasındaki öykü, fizik muayene ve laboratuvar bulguları değerlendirilerek, cerrahi gerektiren rahatsız-lıkların ayırdedilmesinde yardımcı olabilecek verilerin saptanması amaçlanmıştır.…”
unclassified